Clashing Religions in Ancient Egypt - Betrò, Marilina; Miniaci, Gianluca (Brepols, 2025)
What did ‘religion’ mean for the Ancient Egyptians? Was the state involved in acting as a unifying and founding force for Egyptian religion or can we still identify some clashes between different religious practices? To what extent did different rituals, practices, and beliefs intersect and merge across time and space? Such questions have long preoccupied scholars working in the field, but they have often only been considered through the lens of official, ‘centralized’ texts. Yet increasingly, there is an acknowledgement that such texts require calibration from archaeological data in order to offer a more nuanced understanding of how people must have lived and worshipped. The chapters gathered in the volume aim to offer a thorough exploration of Egyptian cultural and religious beliefs, and to explore how these impacted on other areas of daily life. Contributors explore the connection between religion and central power, the paradigms around burial and access to the afterlife, the interconnections between religion, demonology, magic, and medicine, and the impact of multicultural interaction on the religious landscape. What emerges from this discussion is an understanding that the only truly identifiable clash is that between modern, Eurocentric perspectives, and the views of the ancient Egyptians themselves.